Carpocrate et Epiphane chrétiens et platoniciens radicaux - Jurasz, Izabela (2017)
According to ancient authors, Carpocrates and his son Epiphanes were considered to represent a little-known Gnostic doctrine characterised by strong links with Platonic philosophy and libertine morality. Carpocrates became famous as the author of an specific interpretation of the theory of metempsychosis, while Epiphanes – as the exponent of collectivity of goods and women. In spite of their significant differences, both doctrines share a lot of similarities, as they are concerned with the same issues – mainly those discussed by Plato in his “Republic”. The article shows tight connections between Carpocrates and Epiphanes and Christianity, apparent in their usage of Jesus’ logia and of radical expressions derived from the letters by Paul of Tarsus.
Keywords: Gnosis -- Platonism -- New Testament -- metempsychosis -- Carpocrates -- Epiphanes